Business Obstacles-Variances Between Female Owned and Male Owned Enterprises in Lebanon During COVID-19 - Latifa Attieh; Sultana Begum (Eurasian Journal of Management & Social Sciences, 2022)
This research uncovers the variances between female-owned and male-owned enterprises in Lebanon. The World Bank’s Enterprise Survey (ES) focuses on many aspects of the Business Environment. Apart from exploring the Business environment, the ES also collects information about the characteristics of firms, workforce, physical infrastructure, international trade, taxes and corruption, and Business Environment obstacles. In this research, the authors explore the ES data of Lebanon and analyze the variances between the female-owned and male-owned business firms on the top ten business environment obstacles namely, political instability, access to finance, corruption, tax rates, practices of the informal sector, electricity, custom, and trade regulation, Business licenses and permits, inadequately educated workforce and transportation. In addition, variances based on gender where the top manager is male, or female is explored. The Mann-Whitney U test is run to explore the statistical variances (Dodge, 2008). The major findings include that there is statistically significant variance in two variables namely ’Business licensing and permits” and “Environmental Regulation”, among the female-owned and male-owned firms in Lebanon. Another finding includes a statistically significant variance among the two types of firms where the top manager is male or female for the variable “Tax rates”. The study concludes that the most threatening constraints facing enterprises are political instability, access to finance, and corruption in the country, besides that, the COVID-19 pandemic has enlarged the gender gap in terms of increasing and intensifying gender inequality.